Effects of µ-Opioid Receptor Gene Polymorphism on Postoperative Nausea and Vomiting in Patients Undergoing General Anesthesia with Remifentanil: Double Blinded Randomized Trial - Lee, Seung-Hyun; Kim, Joo-Dong; Park, Sol-Ah; Oh, Chung-Sik; Kim, Seong-Hyop (Journal of Korean medical science, 2015)
Association between postoperative nausea and vomiting (PONV) and µ-opioid receptor A118G single nucleotide polymorphism (SNP) is undefined and might underlie inconsistent results of studies on PONV occurrence in patients undergoing general anesthesia with the opioid, remifentanil. Four hundred and sixteen Korean women undergoing breast surgery with general anesthesia were randomized to receive remifentanil 10 ng/mL (plasma-site, Minto model) using a target-controlled infusion device and either propofol for total intravenous anesthesia (T group) or sevoflurane for inhalation anesthesia (I group) with bispectral index values maintained between 40 and 60. Blood specimens were collected after anesthesia induction for A118G SNP analysis. PONV and postoperative pain were evaluated. A118G SNP type distribution among Korean female adults studied was AG (n=195)>AA (n=158)>GG (n=63). Regardless of anesthetic technique, patients with GG types had lower PONV scale on arrival at postoperative care unit (PACU) (P=0.002), while T group showed lower PONV scale than I group up to 6 hr after PACU discharge in AA and AG types. No differences were apparent for postoperative pain among opioid receptor polymorphism. PONV occurrence differs according to opioid receptor polymorphism and anesthetic technique in patients undergoing general anesthesia with remifentanil.